Adjunctive effect of orthokeratology and low dose atropine on axial elongation in fast-progressing myopic children—A preliminary retrospective study. Issue 4 (August 2019) - Chen, Zhi; Huang, Shengmei; Zhou, Jiaqi; Xiaomei, Qu; Zhou, Xingtao; Xue, Feng
Abstract: Purpose: To investigate the adjunctive effect of orthokeratology (ortho-k) and low-dose atropine eye drops on axial length elongation in fast-progressing myopic children. Methods: Axial elongation in 60 eyes of 60 subjects who completed two years of ortho-k treatment was retrospectively reviewed. They were aged between 5.6–11.6 (mean, 8.3 ± 1.5) years old when they started ortho-k treatment. During their first year of ortho-k treatment (Phase One), they all demonstrated a faster than 0.25 mm/yr axial elongation rate. They were then treated with nightly 0.01% atropine in addition to ortho-k treatment for another year (Phase Two). Annual axial elongation rates before and after atropine treatment were compared. Results: Baseline spherical equivalent refractive error was −2.65 ± 1.08 DS and axial length was 24.34 ± 0.92 mm for the study cohort. The mean axial elongation rate was 0.46 ± 0.16 mm/yr during Phase One, being significantly faster in younger children ( t = −4.920, P < 0.001). When atropine was added, annual axial elongation rate significantly decreased to 0.14 ± 0.14 mm/yr ( t = −11.988, P < 0.001), and those who were fast progressors in Phase One had a greater reduction in the rate of axial elongation during Phase Two ( t = −8.052, P < 0.001). Conclusions: Axial elongation rate is faster in younger children undergoing ortho-k treatment. For fast myopia progressors, low dose atropine may significantly slow axial elongation in addition to ortho-k's treatment effect. Those who have faster axial elongation after ortho-k treatment will benefit more from the addition of low dose atropine, regardless of their refractive error and age.